Analisis Paro Hidup dan Keusangan Literatur Artikel Jurnal Kearsipan Tahun 2016-2020 - Dafa, Mohammad Fariq; Pratama, Bayu Indra; Shobaruddin, Muhammad (Jurnal Ilmu Informasi, Perpustakaan, dan Kearsipan, 2022)
This study aims to find out and analyze the half-life and obsolescence of literature in Archival Journal articles for 2016-2020. This study applies a quantitative approach through the half-life analysis method. The population in this study used all samples, namely all articles in the 2016-2020 Archival Journal, which amounted to 54 articles with 1137 citations. Data collection uses digital data archiving techniques. The findings show that, on average, the half-life of literature is 8.6 years and follows the degree of updating of reference sources according to the Ministry of Education and Culture, which mentions reference sources of not more than ten years. Overall, the Archives Journal articles for 2016-2020 show that they are up to date because they are more influenced by new citations with 573 (50.3%%) citations, while obsolete citations with 564 (49.6%) citations. Even so, the use of outdated literature is still significant. Many factors become the reason, such as book citations and laws and regulations have more influence on Archival Journal articles for 2016-2020; limited references to archival knowledge in Indonesian; in addition, it is supported by the relatively slow development of archival science in Indonesia.